Pengaruh Literasi Keuangan Terhadap Perilaku Investasi Milenial di Indonesia - Oktavia Oktavia; Muhammad Riziq Noval; Melani Fitriya Handayani; Rizka Hanipah; Priski Yohana Sihombing (Akuntansi, 2024)
Financial literacy is an individual's ability to understand and manage finances, which plays an important role in making investment decisions. In the context of millennials in Indonesia, financial literacy is a key factor influencing investment behavior, especially in the digital era that provides wide access to various investment instruments such as stocks, mutual funds, and crypto. This journal discusses the relationship between financial literacy and millennial investment behavior by highlighting the importance of financial understanding in managing risk, making rational investment decisions, and driving individual economic growth